Transcrevivências: crítica à colonialidade em ambientes educacionais formais - Santos, Elisson Lima (2024)
By (re) raising and reflecting about my memories from childhood to the present day, mainly within the context of Brazilian formal education environments, both as a student of Northeast region’s Basic Education and Higher Education, as well as a teacher at this level of teaching. I have noticed that (at) these spaces, in which my deviant black body or by the teachers and other people in the school community, modern-colonial violence through education. In this way, infuriated and directing criticism on this issue, with this research, I aim to promote a “transcrevivenciada” (trans-written-lived) analysis that raises transgressions with the violent educational processes generated, reproduced and perpetuated by coloniality in formal educational environments. To this end, I am based on the concept of “escrevivências” generated by Conceição Evaristo to develop an analysis focused on criticism, in dialogue with my parachutes or theoretical references, of modern and colonial educational processes. With this, I point out and I transgress the violence aimed at corporeality that deviates from gender, sexual and racial norms within Brazilian formal educational spaces.